Compensatory Humeral Overgrowth in a Dog - Schulz, K. S.; Davidson, Ellen (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
A severe angular limb deformity secondary to premature closure of the distal ulnar growth plate was diagnosed in a two year old Shetland sheep dog. Radiographic and computerized analysis demonstrated elongation of the ipsi-lateral humerus. The elongation was interpreted as a form of compensatory bone overgrowth similar to that described in the tibia in response to premature closure of femoral growth plates. The regulators of bone growth and possible mechanisms of compensatory overgrowth are reviewed.Compensatory humeral overgrowth secondary to severe antebrachial angular limb deformity was diagnosed in a young Shetland sheep dog. Humeral overgrowth was documented by computerized analysis of digitized humeral radiographs. Potential mechanisms of compensatory overgrowth are reviewed.
Keywords: Compensatory overgrowth; angular limb deformity